2015
DOI: 10.1007/s00792-015-0753-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Mn-catalase and a possible heme peroxidase homologue in protection from oxidative stress in Thermus thermophilus

Abstract: Hydrogen peroxide (H2O2) produces hydroxyl radicals that directly attack a variety of biomolecules and cause severe cellular dysfunction. An extremely thermophilic bacterium, Thermus thermophilus HB8, possesses at least three enzymes that can scavenge H2O2: manganese-containing catalase (TTHA0122, MnCAT), a possible peroxiredoxin homologue (TTHA1300), and a possible heme peroxidase (HPX) homologue (TTHA1714). To investigate the roles of these proteins, we attempted to disrupt each of these genes in T. thermoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although little is known about the role of manganese in stress resistance in Thermus, there is evidence that cellular Mn 2+ concentrations are sufficiently high in Tth, and several Mn 2+ -dependent enzymes have been implicated in the oxidative stress response in this bacterium (54)(55)(56). We found that although Tth Gfh1 is functional in the presence of magnesium ions, its pausestimulatory activity is also greatly enhanced by manganese.…”
Section: Discussionmentioning
confidence: 68%
“…Although little is known about the role of manganese in stress resistance in Thermus, there is evidence that cellular Mn 2+ concentrations are sufficiently high in Tth, and several Mn 2+ -dependent enzymes have been implicated in the oxidative stress response in this bacterium (54)(55)(56). We found that although Tth Gfh1 is functional in the presence of magnesium ions, its pausestimulatory activity is also greatly enhanced by manganese.…”
Section: Discussionmentioning
confidence: 68%
“…An extremely thermophilic bacterium, T. thermophilus , possesses a protein known as MnCAT, which functions as an H 2 O 2 scavenger [ 35 ]. Native MnCAT was purified by heat treatment, followed by several purification steps [ 36 ]. In this study, we investigated the effectiveness of additives on the production of T. thermophilus MnCAT designed to be expressed from the T7 lac promoter in E. coli cells.…”
Section: Resultsmentioning
confidence: 99%